Methodology for calculating an atmospheric pressure-sensitive thermal comfort index PMVaps - Ruivo, Celestino (2021)
Several software tools have been created to calculate the indices Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) by following Fanger's method, which is valid only for atmospheric pressures close to 1 atm. The main objective of this work is to propose a formulation named PMV-PS for predicting an atmospheric pressure-sensitive thermal comfort index (PMVaps). The effort conducted by the authors was focused on the identification of the variables and expressions used in the calculation of thermal comfort index that may be affected by the change of the atmospheric pressure. The best known formulations for each individual aspect were introduced in the new model. It has been calibrated with data at sea level and tested for a set of cases considering different values of metabolic activity rate, thermal resistance of clothing and environmental parameters. At sea level there are negligible differences between PMV and PMVaps. However, when atmospheric pressure deviates from 1 atm, large differences between PMV and PMVaps are observed. PMV-PS model is a good starting point for further investigations into the influence of atmospheric pressure on thermal comfort perception and assessment, under real conditions, or using hypobaric chambers. Moreover, due to the subsisting doubts resulting from the analysis of published studies, it is crucial to perform further experimental work with high statistical significance i) to test the validity of the adopted correlations for the relationship between metabolic rate and atmospheric pressure and ii) to investigate in deep thermal comfort sensation of individuals used to live at altitude and of individuals with short-term exposure to an environment different from what they are used to live. Based upon the main findings of the present work, not considering the atmospheric pressure effect in PMV index may lead to significant errors. (C) 2021 Elsevier B.V. All rights reserved.